Freedom, growth, and the environment - Scott A. Barrett; Kathryn Graddy (Fondazione Eni Enrico Mattei (FEEM), 1998)
A number of recent papers have found that certain measures of pollution worsen and later improve as income per head increases. It is widely believed that the downhill portion of this inverted-U curve reflects an induced policy response; that, as incomes rise, citizens demand improvements in environmental quality, and that these demands are delivered by the political system. In this paper we find that, for a number of pollution variables, an increase in civil and political freedoms significantly improves environmental quality. For other pollution variables, however, we find that freedoms have no effect. The former finding suggests that political reforms may be as important as economic reforms in improving environmental quality worldwide. The latter finding hints that the observation that pollution levels fall with income once income becomes high enough may not always reflect an induced policy response.
Keywords: O13; Q25; 330; Economic growth; Air and water pollution; Civil and political freedoms; Wirtschaftswachstum; Umweltbelastung; Freiheit; USA; Welt